Metformin Attenuates ROS via FOXO3 Activation in Immune Cells - Hartwig, Jelka; Loebel, Madlen; Steiner, Sophie; Bauer, Sandra; Karadeniz, Zehra; Roeger, Carsten; Skurk, Carsten; Scheibenbogen, Carmen; Sotzny, Franziska (Frontiers in Immunology, 2021)
Forkhead box O 3 (FOXO3) is a transcription factor involved in cell metabolism, inflammation and longevity. Here, we investigated if metformin can activate FOXO3 in human immune cells and affects the subsequent level of reactive oxygen/nitrogen species (ROS/RNS) in immune cells. AMP-activated protein kinase (AMPK) and FOXO3 activation were investigated by immunoblot or flow cytometry (FC) analysis, respectively. FOXO3 target gene expression was quantified by real-time PCR. ROS/RNS measurement using dichlorodihydrofluorescein diacetate (DCFH-DA) dye was investigated by FC. The role of the FOXO3 single nucleotide polymorphisms (SNPs) rs12212067, rs2802292 and rs12206094 on ROS/RNS production was studied using allelic discrimination PCR. Metformin induced activation of AMPK (pT172) and FOXO3 (pS413). ROS/RNS level was reduced in immune cells after metformin stimulation accompanied by induction of the FOXO3 targets mitochondrial superoxide dismutase and cytochrome c. Studies in Foxo3 deficient (Foxo3 / ) mouse splenocytes confirmed that metformin mediates its effects via Foxo3 as it attenuates ROS/RNS in myeloid cells of wildtype (WT) but not of Foxo3 / mice. Our results suggest that FOXO3 can be activated by metformin leading to reduced ROS/RNS level in immune cells. This may add to the beneficial clinical effects of metformin observed in large cohort studies on longevity, cardiovascular and cancer risk.